Phytochemical screening and gel stability test of ethanol extract of Chromolaena odorata L. from Indonesia - Handayani, Putri; Yusuf, Hanifa; Gholib, Gholib (Trends in Infection and Global Health, 2024)
Chromolaena odorata L. is a widely used traditional herbal medicine known for its medicinal usage throughout the world. It has been used by the community for its anti-cancer, anti-bacterial, anti-inflammatory, antipyretic, anti-diabetic, and anti-diarrheal, and it also plays a role in hemostasis and wound healing. This study aims to analyze the chemical compounds of C. odorata leaves from Indonesia and to determine the gel stability of its ethanol extract. In this study, C. odorata leaves were collected from Lamkawe Village, Darul Imarah District, Aceh Besar Regency, Aceh, Indonesia. The extraction process was conducted using the maceration method. The active chemical compounds of the ethanol extract of C. odorata leaves were analyzed through phytochemical screening and gas chromatography-mass spectrometry (GC-MS) analysis. The results of the phytochemical screening indicated it contained terpenoids, saponins, flavonoids and phenolics. The most abundant secondary compounds identified were glycidyl palmitate (17.02%), n-9-octadecenoic acid (Z) (15.68%), hexadecanoic acid and l-(+)-ascorbic acid 2,6-dihexadecanoate (12.19%) and 16-hentriacontanone. The 7.5% ethanol extract of C. odorata leaves showed good stability.